2012
DOI: 10.1037/a0028173
|View full text |Cite
|
Sign up to set email alerts
|

Moderators of the feature-positive effect in abstract hypothesis-evaluation tasks.

Abstract: Three studies using abstract materials tested possible moderators of the feature-positive effect in hypothesis evaluation whereby people use the presence of features more than their absence to judge which of two competing hypotheses is more likely. Drawing on a distinction made in visual perception research, we tested whether the feature-positive effect emerges both when using nonsubstitutive features, which can be removed without replacement by other features, and substitutive features, the absence of which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…There is a large Bayesian reasoning literature on how people evaluate evidence to make judgments (e.g., Beach, 1968;Cherubini, Rusconi, Russo, & Crippa, 2013;Cosmides & Tooby, 1996;Fischhoff & Beyth-Marom, 1983;Gigerenzer & Hoffrage, 1995;Hammerton, 1973;McKenzie, 1994;Rusconi, Crippa, Russo, & Cherubini, 2012;Rusconi, Marelli, Russo, D'Addario, & Cherubini, 2013;Rusconi & McKenzie, in press;Slovic & Lichtenstein, 1971;Villejoubert & Mandel, 2002). The issue of whether people's intuitions about the value of obtained evidence align with theoretically optimal models has been the object of recent studies that noted the theoretical and empirical validity of two norms, namely, measures L and Z (e.g., Crupi, Tentori, & Gonzalez, 2007;Fitelson, 2001Fitelson, , 2006Mastropasqua, Crupi, & Tentori, 2010;Tentori, Crupi, Bonini, & Osherson, 2007).…”
mentioning
confidence: 99%
“…There is a large Bayesian reasoning literature on how people evaluate evidence to make judgments (e.g., Beach, 1968;Cherubini, Rusconi, Russo, & Crippa, 2013;Cosmides & Tooby, 1996;Fischhoff & Beyth-Marom, 1983;Gigerenzer & Hoffrage, 1995;Hammerton, 1973;McKenzie, 1994;Rusconi, Crippa, Russo, & Cherubini, 2012;Rusconi, Marelli, Russo, D'Addario, & Cherubini, 2013;Rusconi & McKenzie, in press;Slovic & Lichtenstein, 1971;Villejoubert & Mandel, 2002). The issue of whether people's intuitions about the value of obtained evidence align with theoretically optimal models has been the object of recent studies that noted the theoretical and empirical validity of two norms, namely, measures L and Z (e.g., Crupi, Tentori, & Gonzalez, 2007;Fitelson, 2001Fitelson, , 2006Mastropasqua, Crupi, & Tentori, 2010;Tentori, Crupi, Bonini, & Osherson, 2007).…”
mentioning
confidence: 99%
“…Rather, the greater difficulty in belief updating in light of the answers to the asymmetrically disconfirming question reveals people's tendency to overweigh the evidential strength of "yes" versus "no" answers. We found this form of the feature-positive effect (e.g., Cherubini et al, in press;Jenkins & Sainsbury, 1969, 1970Newman et al, 1980;Rusconi, Crippa, et al, 2012; Rusconi et al, in press) in both experiments, as revealed by the significant main effects of answer. This finding is in keeping with previous similar experiments (Slowiaczek et al, 1992, Experiments 1A, 2B, and 2C).…”
mentioning
confidence: 57%
“…In this example we consider two exhaustive and mutually exclusive hypotheses, therefore an answer confirms one hypothesis to the same extent as it disconfirms the other (e.g., Nelson, 2005;Nickerson, 1996). Accordingly, in this example, the formula for Impact reduces to the absolute value of the difference between the posterior probability of either hypothesis and .5 (that is, the prior probability of either hypothesis).…”
Section: How To Evaluate the Informativeness Of Answersmentioning
confidence: 99%
See 2 more Smart Citations